On the relationship between corporate governance and value creation in an economic crisis: Empirical evidence for the Spanish case - Mónica Villanueva-Villar; Elena Rivo-López; Santiago Lago Pe\~nas (BRQ Business Research Quarterly, 2016)
This paper analyses the effect of corporate governance on value creation. It relies upon a dataset that includes the companies listed on the Spanish Stock Exchange for the period from 2005 to 2012. Attention is focused on the structure and composition of boards. In particular, four variables are analyzed: BOARD_SIZE, BOARD_INDEPENDENCE, BOARD_DILIGENCE (measured by the number of meetings), and DUALITY (chairman and chief executive officer being the same person). Over the period of the deepest economic crisis (2009–2012) the most significant variables that had a positive effect on value creation were BOARD_INDEPENDENCE and BOARD_SIZE. Hence, the global financial crisis has highlighted the need for effective corporate governance. Policy makers should think about translating the recommendations of the Good Governance Codes into legislation (mandatory), to improve corporate governance."
Keywords: 650; Corporate governance; Value creation; Board; Economic crisis; Independence